ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DITINJAU DARI KECERDASAN SPASIAL - Nurkahfiah Ridwan; Ruslan; Hisyam Ihsan (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
The study aims at discovering the description of problem-solving skills of students in Math based on spatial intelligence in grade VIII at SMPN 3 Pallangga. This type of study is qualitative research with a descriptive approach. The research subjects were 6 students who were divided into 3 groups, namely 2 subjects with high spatial skills, 2 subjects with moderate spatial skills, and 2 subjects with low spatial skills in grade VIIIC at SMPN 3 Pallangga. The research instruments were the researcher herself as the main instrument and a test of spatial intelligence, the test of problem-solving skills, a guided interview, and a validation sheet as the supporting instruments. The data collecting method employed a written test and interview. The data analysis was conducted by employing data condensation, data presentation, and conclusion drawing. The data validity employed a source triangulation. Through the qualitative data analysis, the researcher discovered that the Math problem-solving skills of students with high spatial intelligence understood the problem by using spatial visualization skills, spatial perception, and mental rotation, as well as able to solve the problem by fulfilling Polya's four steps correctly. The Math problem-solving skills of students with moderate spatial intelligence understood the problems by using spatial visualization skills and spatial perception and were able to solve the problem by fulfilling Polya's two steps only, as well as being unable to plan the solution and rechecking. The Math problem-solving skills of students with low spatial intelligence still have difficulties using their spatial skills so they are unable to solve the problem given correctly.